BE-P32: fabrication of Nahar Seed Oil for biolubricant production - Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Qudsieh, Isam Y.; Ibrahim, Irmanisha (2012)
In this study, a laboratory scale for extraction and analysis of Nahar (Mesua ferrea L.) seed oil (NSO) for biolubricant production was conducted. The oil was extracted then analyzed the chemical and physical properties and studied its current and potentially future use in lubricant applications, as both base oil and additives. The analysis includes moisture content, free fatty acids (FFA%), saponification value (SV), iodine value (IV), unsapoifiable matters and phosphorus content. After that the NSO was undergo an esterification process and two-step transesterification processes to increase its viscosity for production of biolubricant. The reaction temperature, the reaction time, and the catalyst dosage (sodium methoxide) were the chosen parameters in the optimization processes of the Nahar seed oil (NSO) biolubricant production. From the result obtained, the maximum viscosity of NSO biolubricant was achieved when the temperature was 150oC, 80 min in reaction time and 0.8% catalyst dosage.